Analisis Faktor-faktor yang Mempengaruhi Persepsi Pelaku Usaha Mikro Kecil Menengah Tentang Pentingnya Pelaporan Keuangan Serta Prospek Implementasi SAK ETAP - Abdul Malik Hakim; Noer Sasongko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify the factors influencing the perceptions of Micro, Small, and Medium Enterprises (MSMEs) in Sukoharjo District regarding the importance of preparing financial statements based on the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The study employs a quantitative approach with a descriptive and causal associative research design. A total of 100 respondents were selected as the sample using the convenience sampling method. The independent variables in this study include education level, accounting knowledge, business duration, and business size, while the dependent variable is the perception of the importance of financial statements based on SAK ETAP. The analysis results indicate that education level influences perceptions at a 10% significance level, accounting knowledge and business size significantly affect MSMEs’ perceptions, while business duration does not have a significant impact.